Cholinesterase in different types of the muscle tissue during the early postmortem period for diagnosis of death coming - Cherkashyna, Lidiya; Shklyar, Anton; Sukhonosov, Roman; Miroshnikova, Olha; Naguta, Lyudmyla; Olkhovskiy, Vasyl; Demikhova, Nadiia; Kuts, Larysa; Barchan, Ganna; Sukhomlyn, Ganna; et al. (Bangladesh Journal of Medical Science, 2021)
The purpose of the research: consisted in study of postmortem regularities in the content of cholinesterasein different types of muscle tissue (MT) for improving accuracy of determination of the prescriptionof death coming PDC. Materials and methods: The activity/level of cholinesterase was determinedin homogenates of the myocardial (MMH), oesophageal (OMH), diaphragm (DMH) and intercostalmuscles (IMH)within the early PMP (3-13 hours after the coming of death) on 30 human corpses. MTwas sampled in conditions of postmortem biopsy with use of special instruments; MT homogenateswere prepared following the standard technique with subsequent determination of cholinesterase content in MT homogenates. Results and discussion: The analysis of postmortem changes in the content ofcholinesterase in MT depending upon PDC revealed that after 3 hours from the moment of death comingits highest content was in muscles of the oesophagus, the least one being in MT of the intercostal muscles(respectively, (2,717.1±37.1) and (883.5±6.2) U/g, р<0.001). Levels of cholinesterase content in MT ofthe myocardium and diaphragm were rather close, though they differed (respectively, (1,213.8±8.8) and(1,512.8±11.5) U/g, р<0.05), and occupied an intermediate place between the corresponding values of MTof the intercostal muscles and oesophagus.A common pattern for the content of cholinesterase in differenttypes of MT was characterized by a decrease of this content with an increase in PDC terms; besides, thedynamic lines of its changes, that we obtained, became basic ones for substantiating quantitative timedependencies and construction of relevant nomograms for forensic diagnosis of PDC by cholinesterase content in MT. Conclusions: It was proved that the content of cholinesterase in all MT homogenates,which we studied, changed regularly (and nonlinearly), but the initial and final levels of cholinesterasecontent differed depending upon the type of MT. Besides, the dynamics in changes of the content ofcholinesterase within the time period of 3÷13 hours from the moment of death coming differed uponthe type of MT too. Advantages of the technique consist in theintegrity of biochemical examinationof different types of MT and simplicity in interpretation of findings. The application of the nomogramtechnique for assessing PDC by cholinesterase content in MT makes it possible to improve the accuracyof diagnosis for terms of the coming of death up to 60 minutes. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.95-100